2016
DOI: 10.1016/j.ejpal.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Lineup identification accuracy: The effects of alcohol, target presence, confidence ratings, and response time

Abstract: Despite the intoxication of many eyewitnesses at crime scenes, only four published studies to date have investigated the effects of alcohol intoxication on eyewitness identification performance. While one found intoxication significantly increased false identification rates from target absent showups, three found no such effect using the more traditional lineup procedure. The present study sought to further explore the effects of alcohol intoxication on identification performance and examine whether accurate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…For example, moderately intoxicated participants in an old-new face recognition experiment were found to make more false identifications of same-race faces than sober controls, a reduction of the own-race face processing bias the study's authors attribute to alcohol disrupting the expert encoding of same-race faces (Hilliar, Kemp & Denson, 2010). Among studies incorporating more forensically relevant face memory tasks (Altman, Schreiber Compo, McQuiston, Hagsand, & Cervera, 2018;Bayless, Harvey, Kneller, & Frowd, 2018;Colloff & Flowe, 2016;Dysart, Lindsay, MacDonald, & Wicke, 2002;Flowe et al, 2017;Hagsand, Roos af Hjelmsäter, Granhag, Fahlke, & Söderpalm-Gordh, 2013a;Harvey, Kneller, & Campbell, 2013a;Kneller & Harvey, 2016;Read, Yuille, & Tollestrup, 1992;Yuille & Tollestrup, 1990), three reveal an adverse effect of alcohol intoxication on identification accuracy (Bayless et al, 2018;Dysart et al, 2002;Read et al, 1992). Read et al (1992, Experiment 2) found an alcohol-linked reduction in face identification accuracy, but from a mock-perpetrator rather than mock-witness perspective.…”
mentioning
confidence: 99%
“…For example, moderately intoxicated participants in an old-new face recognition experiment were found to make more false identifications of same-race faces than sober controls, a reduction of the own-race face processing bias the study's authors attribute to alcohol disrupting the expert encoding of same-race faces (Hilliar, Kemp & Denson, 2010). Among studies incorporating more forensically relevant face memory tasks (Altman, Schreiber Compo, McQuiston, Hagsand, & Cervera, 2018;Bayless, Harvey, Kneller, & Frowd, 2018;Colloff & Flowe, 2016;Dysart, Lindsay, MacDonald, & Wicke, 2002;Flowe et al, 2017;Hagsand, Roos af Hjelmsäter, Granhag, Fahlke, & Söderpalm-Gordh, 2013a;Harvey, Kneller, & Campbell, 2013a;Kneller & Harvey, 2016;Read, Yuille, & Tollestrup, 1992;Yuille & Tollestrup, 1990), three reveal an adverse effect of alcohol intoxication on identification accuracy (Bayless et al, 2018;Dysart et al, 2002;Read et al, 1992). Read et al (1992, Experiment 2) found an alcohol-linked reduction in face identification accuracy, but from a mock-perpetrator rather than mock-witness perspective.…”
mentioning
confidence: 99%
“…Previous studies provide some support for this idea, as indicated by lower overall postdecision confidence ratings in intoxicated versus sober participants, independent of decision accuracy (Flowe et al, ; Harvey et al, ; Yuille & Tollestrup, ). Others, however, have not found such an effect (Dysart et al, ; Hagsand et al, ; Kneller & Harvey, ). In essence, optimality hypothesis predicts a two‐way interaction between identification accuracy and intoxication for confidence (i.e., a stronger confidence–accuracy relationship for sober than intoxicated witnesses; Hypothesis 3b).…”
Section: Introductionmentioning
confidence: 94%
“…Testing typically took place with a delay of 1 or 7 days. Under such artificially restrictive conditions, correct and false identification rates were consistently unaffected by alcohol intoxication (Flowe et al, ; Hagsand, Roosaf Hjelmsäter, Granhag, Fahlke, & Söderpalm‐Gordh, ; Harvey, Kneller, & Campbell, ; Kneller & Harvey, ; Yuille & Tollestrup, ). Read, Yuille, and Tollestrup (, Experiment 2) constitute an exception in that they found adverse effects of intoxication on correct identifications when level of arousal was low, but not when level of arousal was high; there was no effect on false identification rates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations